Employee-Inventor’s Right to Compensation in Patent Law System in Indonesia and some Countries - ROISAH, Kholis (Journal of Advanced Research in Law and Economics, 2019)
The understanding of the regulation of compensation system gives a picture of how an owner of a corporation determines his/her business strategy as well as avoiding conflict with employees. For employees, it is important to understand how the corporation regulates the compensation system so that they know their rights. Understanding compensation system also encourages employees to be innovative. This study is about compensation to employee inventor and the regulation of how the compensation is granted and how much the corporation spends to compensate their employee inventors. The regulation of compensation system for employee inventors in Indonesia has not been regulated clearly and measurably in patent law as well as in labor legislation. In some other countries (Japan, South Korea, China, French and Germany), the regulation of compensation system is a mandatory rule in nature, and even the regulation of mechanism, the amount and the institutional system of the compensation have been well regulated in their patent, labor or manpower, employee inventions and innovation, and technology promotion law. The regulation of the right to compensation that is clear and measurable in some top rank countries has been proven to be able to boost not only innovation climate and promotion of Science and technology, but also economy growth.